Genetic and Clinical Characteristics of Patients with Vitamin D Dependent Rickets Type 1A - Fatma Dursun; Gamze Özgürhan; Heves Kırmızıbekmez; Ece Keskin; Bülent Hacıhamdioğlu (Galenos Yayincilik, 2019)
Objective:Vitamin D dependent rickets type 1A (VDDR1A) is an autosomal recessive disorder caused by mutations in the 1α-hydroxylase gene (CYB27B1). As it may be confused with nutritional rickets and hypophosphatemic rickets, genetic analysis is important for making a correct diagnosis.Methods:We analysed genomic DNA from 11 patients from eight different Turkish families. The patients were recruited for our studies if they presented with a diagnosis of VDDR.Results:The mean ± standard deviation age at diagnosis was 13.1±7.4 months. Seven patients had mild hypocalcemia at presentation while four patients had normal calcium concentrations. All patients underwent CYP27B1 gene analysis. The most prevalent mutation was the c.195 + 2T>G splice donor site mutation, affecting five out of 11 patients with VDDR1A. Two patients from the fourth family were compound heterozygous for c.195 + 2T>G and c.195 + 2 T>A in intron-1. Two patients, from different families, were homozygous for a previously reported duplication mutation in exon 8 (1319_1325dupCCCACCC, Phe443Profs*24). One patient had a homozygous splice site mutation in intron 7 (c.1215 + 2 T>A) and one patient had a homozygous mutation in exon 9 (c.1474 C>T).Conclusion:Intron-1 mutation was the most common mutation, as previously reported. All patients carrying that mutation were from same city of origin suggesting a "founder" or a "common ancestor" effect. VDDR1A should definitely be considered when a patient with signs of rickets has a normal 25-OHD level or when there is unresponsiveness to vitamin D treatment.